Updates in The Role of MRI in Diagnosis and Staging of Pancreatic Cancer: A Systematic Review - Jubran Salem Alkhalidy, Amani; Ibrahim Hadi Matabi, Atheer; Ali Al Rayshan, Hadi; Mansoor Hagawi, Fatimah; Saeed Mohammed Alyami, Mohammed; tifa Ibrahim Shami, Duaa; Mofareh Jaber Huraysi, Waad; Ahmed Mahdi Alsaadi, Hamad; Nattash Alzamanan, Mohammed; Salem Harml Bnisalman, Hassan (International Journal of Life Science and Pharma Research, 2022)
Abstract: Pancreatic cancer is the fourth leading cancer-related cause of death throughout the world. Magnetic resonance imaging (MRI) is typically capable of quickly differentiating cystic from noncystic tumours due to the good soft tissue contrast resolution. Cystic tumours are frequently simple to identify with an MRI; however, non-cystic non-adenocarcinoma tumours can exhibit a wide range of imaging characteristics that may be mistaken for ductal adenocarcinoma. An effective method for identifying pancreatic lesions is MRI. This study investigates the current and recent evidence concerning the role of MRI in the diagnosis and staging of pancreatic cancer. PubMed, Web of Science, Science Direct, EBSCO, and Cochrane library were searched. Study articles were screened by title and abstract using Rayyan QCRI then a full-text assessment was implemented. A total of 7 studies were included, with 618 pancreatic cancer patients with different histopathological types. Most studies reported the benefits of MRI in the diagnosis and staging of pancreatic cancer and in identifying extra-abdominal metastases. Only one study found that MRI understaged the tumor size and did not detect the micro-infiltration of peri-pancreatic tissues. MRI has a significant role in diagnosing and staging pancreatic cancer. There have lately been substantial advancements in pancreatic imaging utilizing multiple imaging modalities, such as SG-KS-4D-MRI and DW imaging with traditional MR.